PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA PADA MATA PELAJARAN GEOGRAFI KELAS X DI SMA NEGERI 1 GUNUNG TALANG - Prasantika, Arsih; Suasti, Yurni (JURNAL BUANA, 2024)
The research aims to determine the application of differentiated learning in the independent curriculum in geography subjects at SMA Negeri 1 Gunung Talang. This type of research uses a qualitative appoarch. Data collection techniques are observation, interviews, and document study. The data analysis technique is an interactive model. The results is application of differentiated started from pre-learning activities carried out by guidance and conseling teachers to determine learning styles. planning in the form of teaching modules and learning outcomes is designed jointly by geography teacher. Content in the form of PPT, Book, Videos, and Loud voices. The learning models are PJBL, PBL, and Inquiry Learning. Learning is interactive, inspiring, facilitatory, fun, challenging, motivating, and provides sufficent space for initiative, creativity, according to student talents, interests and abilities. The products by studentsare Notes, PPTs, and Mindmaps.